Beneficial rhizobacterium provides positive plant–soil feedback effects to Ageratina adenophora - Yuan-yuan SUN; Qiu-xin ZHANG; Yun-peng ZHAO; Yue-hui DIAO; Fu-rong GUI; Guo-qing YANG (Journal of Integrative Agriculture, 2021)
Rhizosphere microbial communities play important roles in facilitating or inhibiting the establishment of exotic species. Since some invasive plants interact with soil microbial communities such as rhizosphere bacteria, changes triggered by rhizosphere bacteria may alter competitive interactions between exotic and native plants. This study compared the Bacillus cereus content in soils with different degrees of Ageratina adenophora invasion, and investigated the effects of A. adenophora allelochemicals on B. cereus growth and soil characteristics and the feedback effects of B. cereus on A. adenophora growth. Bacillus cereus content in the rhizosphere of A. adenophora increased with intensification of the invasion process, and newly invaded soil contained almost twice as much bacteria as noninvaded soil. When rhizosphere soil was added to the root exudates of A. adenophora, the contents of B. cereus were twice as much as the control, except on the first day. Certain soil parameters increased significantly, such as ammonium nitrogen (NH4+-N) and available phosphorus (AP), which were increased by 41 and 27%, respectively. Soil treatment with B. cereus promoted the degradation of two allelochemicals from the rhizosphere of A. adenophora, amorpha-4,7(11)-dien-8-one and 6-hydroxy-5-isopropy1-3,8-dimethyl-4a,5,6,7,8,8a-hexahydraphthalen-2(1H)-one, to varying degrees; and increased the germination rate by 50%, root length by 117%, shoot length by 48% and fresh weight by 81% for A. adenophora compared to those of untreated soil. Our results confirmed that the invasion of A. adenophora will promote an increase of B. cereus, a beneficial rhizosphere bacterium, which in turn induces a positive feedback effect on A. adenophora.